Interactive Teaching Strategies for Online English Speaking Classes: Engaging Primary Students - Aisy, Ghina Rohadatul; Imani, Anugrah; Kurniawati, Nia; Sulaeman, Dedi; Rohaedi, Tedi (Universitas Muhammadiyah Barru, 2025)
This study investigated how teachers implemented interactive teaching strategies to increase the engagement of 15 elementary school students aged 7-10 years in an online English-speaking class. Using a qualitative case study approach, data was collected through observing one online class session conducted using Zoom Meetings. Thematic analysis identified various strategies, such as the use of multimedia (movies), interactive platforms (Quizizz), and structured participation methods (e.g., gender-based turn-taking). Repetition techniques were also found to be a tool to reinforce learning. The results of this study show that interactive strategies are able to improve students' engagement and speaking skills in an online environment. This research provides practical recommendations for educators in creating engaging and effective learning experiences in the online classroom.